Pengaruh Pendekatan RME (Realistic Mathematics Education) Terhadap Kemampuan Koneksi Matematis Siswa Kelas VIII MTs Al-Aziziyah Putri Kapek Gunungsari - Kemuning Wismayani; Arjudin Arjudin; Nani Kurniati; Ketut Sarjana (Pendidikan Matematika FKIP Universitas Mataram, 2023)
The research aims to describe the effect of the RME (Realistic Mathematics Education) approach on students' mathematical connection abilities of class VIII MTs. Al-Aziziyah Putri Kapek Gunungsari for the 2022/2023 school year. This research is experimental research using a posttest-only control group design. The population in this study was all class VIII with a total of 7 classes. While the sample in this study there were 2 classes, namely class VIII-7 as the experimental class and VIII-6 as the control class. The sampling technique used is cluster random sampling. Data collection was carried out using a mathematical connection ability test. The data obtained were processed with SPSS. The results of the statistical analysis showed that the test results of the students' mathematical connection abilities with the RME approach are higher than conventional learning. This can be seen from the average value of the experimental class 65 and the control class 56.57. The results of the data analysis shows. The value means that there is an influence of the RME approach on the students' mathematical connection abilities. The magnitude of the influence given is 5.75%, which means that the effect of the RME approach on the ability of mathematical connections is not large.